2013
DOI: 10.3109/09513590.2013.819083
|View full text |Cite
|
Sign up to set email alerts
|

Is Letrozole needed for controlled ovarian stimulation in patients with estrogen receptor-positive breast cancer?

Abstract: SummaryObjective: To assess the advantages and disadvantages of using Letrozole for controlled ovarian stimulation (COH) in young patients with estrogen receptorpositive (ER+) breast cancer, wishing to cryopreserve oocytes. Design: Retrospective cohort analysis.Setting: Sixteen Italian Units for Reproductive Medicine and In Vitro Fertilization.Methods: Data of 50 ER+ breast cancer patients undergoing COH to cryopreserve oocytes before gonadotoxic chemotherapy with a Letrozole plus gonadotropins (Le+Gn) protoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
43
3
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 29 publications
6
43
3
4
Order By: Relevance
“…On the first point, alternative approaches for ovarian stimulation with the use of letrozole [24] or tamoxifen [25] have been developed for patients with breast cancer with no observed negative consequence on the quality of the oocytes and embryos collected [25,26]. Furthermore, one small retrospective study suggests no clear detriment from ovarian stimulation with concurrent administration of letrozole and gonadotropins before chemotherapy on breast cancer prognosis [27].…”
Section: Key Pointsmentioning
confidence: 97%
“…On the first point, alternative approaches for ovarian stimulation with the use of letrozole [24] or tamoxifen [25] have been developed for patients with breast cancer with no observed negative consequence on the quality of the oocytes and embryos collected [25,26]. Furthermore, one small retrospective study suggests no clear detriment from ovarian stimulation with concurrent administration of letrozole and gonadotropins before chemotherapy on breast cancer prognosis [27].…”
Section: Key Pointsmentioning
confidence: 97%
“…Conflicting results have been reported regarding the number of mature oocytes yielded in letrozole-associated COH compared to patients undergoing COH without letrozole 48,49 . Nonetheless, in 2015, Oktay, et al reported the success rate of oocytes/embryos cryopreservation using letrozole-associated COH in the largest breast cancer cohort reported to date 45 .…”
Section: Letrozole-associated Controlled Ovarian Hyperstimulationmentioning
confidence: 77%
“…However, even when implementing this triggering threshold, high rate of oocyte immaturity was still described by other groups [19,58]. Additionally, in a retrospective cohort study of 16 IVF units, a significantly lower oocyte yield in patients treated with this protocol was observed [59]. In terms of safety, although E2 reduction is clearly achieved when using letrozole, some patients still exhibit levels which are higher than those observed during a natural ovulatory cycle.…”
Section: Estrogen Exposurementioning
confidence: 95%